2022
DOI: 10.3390/plants11101385
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spermidine in Photosynthesis and Polyamine Metabolism in Lettuce Seedlings under High-Temperature Stress

Abstract: High temperature is a huge threat to lettuce production in the world, and spermidine (Spd) has been shown to improve heat tolerance in lettuce, but the action mechanism of Spd and the role of polyamine metabolism are still unclear. The effects of Spd and D-arginine (D-arg) on hydroponic lettuce seedlings under high-temperature stress by foliar spraying of Spd and D-arg were investigated. The results showed that high-temperature stress significantly inhibited the growth of lettuce seedlings, with a 33% decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…(2016) . Recently, in heat-stressed lettuce, He et al. (2022) have also observed significant alleviation in the parameters P n , C i , g s , E , F v / F m , qP, and ETR with Spd application, which resulted in improved growth, water use efficiency, and biomass production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2016) . Recently, in heat-stressed lettuce, He et al. (2022) have also observed significant alleviation in the parameters P n , C i , g s , E , F v / F m , qP, and ETR with Spd application, which resulted in improved growth, water use efficiency, and biomass production.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, in heat-stressed lettuce, He et al (2022) have also observed significant alleviation in the parameters P n , C i , g s , E, F v / F m , qP, and ETR with Spd application, which resulted in improved growth, water use efficiency, and biomass p r od u c t i o n . I m p r o v e d c hl o r o p h y l l s y n t h e s i s a n d photosynthesis in NO-and Spd-treated plants can directly influence the carbon metabolism and the carbon-nitrogen balance (Du et al, 2016;Farag et al, 2017), which will otherwise be drastically affected by Ni stress (Sheoran et al, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…In cotton, exogenous D-Arg can significantly reduce endogenous Put levels, thereby lowering PAs level [11]. In lettuce, the application of D-Arg can reduce endogenous PAs level and reduce the tolerance of lettuce seedlings to high temperatures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Parameters of photosynthesis (A, g s , E, etc.) [13,14], dynamics of chlorophyll fluorescence (F v /F m , Y(II), qP, etc.) [15,16], and solarinduced chlorophyll fluorescence (SIF) [17,18] are considered valuable indicators to reveal the physiological regulatory effects of the photosynthetic system under temperature stress.…”
Section: Introductionmentioning
confidence: 99%